Indigenous knowledge and curriculum internationalization for sustainability: A decade of global scientometric evidence - Kumar, Vinodh; Thakur, Khusbu (Journal of International Students, 2026)
This study presents a global scientometric analysis of how Indigenous Knowledge (IK) is integrated into higher-education curricula for internationalization and sustainability (2016–2025). Using Scopus data and science-mapping tools (Bibliometrix/Biblioshiny and VOSviewer), the analysis examines annual publication trends, leading countries and institutions, collaboration patterns, and the field’s conceptual structure. Findings reveal limited activity until 2018, followed by steady growth and a sharp rise after 2022. The United States, Australia, Canada, South Africa, Brazil, and Indonesia emerge as primary contributors. Keyword and thematic analyses identify tightly connected clusters centered on IK, sustainability, higher education, teacher education, climate change, and curriculum decolonization. The study shows that IK is evolving from a locally bounded practice into a globally networked knowledge domain that supports Sustainable Development Goals 4.7 and 13 while redefining internationalization through epistemic plurality and curriculum justice, providing an empirical foundation for policy and practice in internationalized, sustainability-oriented higher education.